Collisions of FeO+ with H2 and He in a Cryogenic Ion Trap. Issue 22 (6th October 2016) - Gerlich, Dieter; Jašík, Juraj; Andris, Erik; Navrátil, Rafael; Roithová, Jana
Abstract: The nominal temperature range of cryogenic radio‐frequency ion traps has recently been extended down to T= 2.3 K. Whereas in situ He tagging of mass‐selected ions embedded in dense helium buffer gas is becoming common for recording IR spectra through photofragmentation of small and large ions, much less activity is devoted to the field of cold chemistry, which in this contribution means the two orders of magnitude extending from 300 to below 3 K. The importance of this temperature range for understanding the dynamics of bi‐ and termolecular reactions is illustrated with new results for the time‐honored reaction of FeO + with H2 obtained with the cryogenic ion trap ISORI in Prague. The rate coefficient for forming Fe + +H2 O increases steeply with decreasing temperature. In addition more product channels open up, such as the stabilized reaction‐intermediate complexes H2 FeO + and He n –FeO + formed by ternary association with He. For the FeOH + +H channel only a minor signal is observed. The rate coefficients provide deep insight into lifetimes, bottlenecks, and barriers impeding almost completely the exothermic, but spin‐forbidden, reaction at room temperature. For some of the He‐tagged ions, IR predissociation spectra are recorded. A breakthrough is obtaining the first spectrum of [(H2 )FeO] +, synthesized and tagged in situ with He. These results pave the way to study the structures of reaction intermediates stabilized in the gas phase by means of collisions with helium. Abstract : Trapped in the cold : The versatility of ISORI, a tandem quadrupole mass spectrometer with a cryogenic ion trap at its heart (see figure), is exploited to study the interaction of FeO + with H2 and He buffer gas from room temperature to nominal temperatures below 3 K. Furthermore, the use of He tagging for recording IR spectra is investigated.